Prevalence and abundance of insect pests in stored pulses collected from two local markets of Dhaka city (Jahangirnagar University Journal of Biological Sciences, 2019)
Prevalence and abundance of stored grain insect pests in four varieties of pulses i.e. Lens culinaris, Pisum staivum, Cicer arietinum collected from two markets of Dhaka city were recorded. Nine species of insect pests, viz. Sitophilus oryzae, Tribolium castaneum, Callosobruchus chinensis, C. maculatus, Rhizopertha dominica, Oryzaephilus surinamensis, Liposcelis entomophila, Sitotroga cerealella, and Formica sp., were recorded throughout the study. The percentage of weight-loss was higher (7.54) in those pulses which were highly infested by pests. Highest pest population was observed during May to June (753). However, Sitotroga cerealella were found only in November to December of the study period. The maximum species richness (7) was observed in Green gram and Chickpeas samples, but the minimum species evenness was observed in Green gram (0.6969) and maximum in Red lentil (0.9886).Jahangirnagar University J. Biol. Sci. 8(1): 75-82, 2019 (June)